The roles of serine hydrolases and serum albumin in alisol B 23-acetate hydrolysis in humans - Zhang, Tiantian; Zhang, Feng; Zhang, Yani; Li, Hongxin; Zhu, Guanghao; Weng, Taotao; Huang, Cheng; Wang, Ping; He, Yuqi; Hu, Jing; Ge, Guangbo (Frontiers in Pharmacology, 2023)
Alisol B 23-acetate (AB23A), a major bioactive constituent in the Chinese herb Zexie (Rhizoma Alismatis), has been found with multiple pharmacological activities. AB23A can be readily hydrolyzed to alisol B in mammals, but the hydrolytic pathways of AB23A in humans and the key enzymes responsible for AB23A hydrolysis are still unrevealed. This study aims to reveal the metabolic organs and the crucial enzymes responsible for AB23A hydrolysis in human biological systems, as well as to decipher the impact of AB23A hydrolysis on its biological effects. The results clearly demonstrated that AB23A could be readily hydrolyzed to alisol B in human plasma, intestinal and hepatic preparations, while human butyrylcholinesterase (hBchE) and human carboxylesterases played key roles in AB23A hydrolysis in human plasma and tissue preparations, respectively. It was also found that human serum albumin (hSA) could catalyze AB23A hydrolysis, while multiple lysine residues of hSA were covalently modified by AB23A, suggesting that hSA catalyzed AB23A hydrolysis via its pseudo-esterase activity. Biological tests revealed that both AB23A and alisol B exhibited similar FXR agonist effects, indicating AB23A hydrolysis did not affect its FXR agonist effect. Collectively, this study deciphers the hydrolytic pathways of AB23A in human biological systems, which is very helpful for deep understanding of the metabolic rates of AB23A in humans, and useful for developing novel prodrugs of alisol B with desirable pharmacokinetic behaviors.